Integrated metabolome and transcriptome analysis reveals salicylic acid and flavonoid pathways’ key roles in cabbage’s defense responses to Xanthomonas campestris pv. campestris - Sun, Qingguo; Xu, Zhongmin; Huang, Wei; Li, Dawei; Zeng, Qi; Chen, Lin; Li, Baohua; Zhang, Enhui (Frontiers in Plant Science, 2022)
Xanthomonas campestris pv. campestris (Xcc) is a vascular bacteria pathogen causing black rot in cabbage. Here, the resistance mechanisms of cabbage against black rot were explored by integrated metabolome and transcriptome analysis. Pathogen perception, hormone metabolisms, sugar metabolisms and phenylpropanoid metabolisms in cabbage were systemically re-programmed in both transcriptional and metabolic levels after Xcc infection. Notably, salicylic acid (SA) metabolism pathway was highly enriched in resistant line following Xcc infection, indicating that SA metabolism pathway may positively regulate the resistance of Xcc. Moreover, we also validated our hypothesis by showing the flavonoid pathway metabolites chlorogenic acid and caffeic acid could effectively inhibit the growth of Xcc. Our results provided valuable insights and resource dataset for further exploring Xcc-cabbage interactions, and help uncover molecular breeding targets for black rot resistant variety in cabbage.